2022
DOI: 10.1038/s42003-022-04265-0
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterium tuberculosis senses host Interferon-γ via the membrane protein MmpL10

Abstract: Mycobacterium tuberculosis (Mtb) is one of the most successful human pathogens. Several cytokines are known to increase virulence of bacterial pathogens, leading us to investigate whether Interferon-γ (IFN-γ), a central regulator of the immune defense against Mtb, has a direct effect on the bacteria. We found that recombinant and T-cell derived IFN-γ rapidly induced a dose-dependent increase in the oxygen consumption rate (OCR) of Mtb, consistent with increased bacterial respiration. This was not observed in a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…In addition to these, the transcript levels of Erdman_0321 (Rv0287, esxG ), a protein involved in the inhibition of phagosome maturation and pathogenesis of M. tuberculosis , were also reduced in the Δ menT4 Δ T3 strain (Supplementary Data 1 ) 40 . As shown in Supplementary Data 1 , the levels of transcripts encoding for proteins essential for growth (Erdman_3437 (Rv3137), Erdman_3739 (Rv3418c), stress adaptation (Erdman_0630 (Rv0574c), Erdman_2884 (Rv2624c)) and interaction with host Interferon-γ (IFN-γ) (Erdman_1325, Rv1183) were also reduced in Δ menT4 Δ T3 strain relative to the parental strain 36 , 41 44 . Several studies have reported that replacing an open reading frame with an antibiotic selection marker might affect the expression of neighboring genes due to the polar effect.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to these, the transcript levels of Erdman_0321 (Rv0287, esxG ), a protein involved in the inhibition of phagosome maturation and pathogenesis of M. tuberculosis , were also reduced in the Δ menT4 Δ T3 strain (Supplementary Data 1 ) 40 . As shown in Supplementary Data 1 , the levels of transcripts encoding for proteins essential for growth (Erdman_3437 (Rv3137), Erdman_3739 (Rv3418c), stress adaptation (Erdman_0630 (Rv0574c), Erdman_2884 (Rv2624c)) and interaction with host Interferon-γ (IFN-γ) (Erdman_1325, Rv1183) were also reduced in Δ menT4 Δ T3 strain relative to the parental strain 36 , 41 44 . Several studies have reported that replacing an open reading frame with an antibiotic selection marker might affect the expression of neighboring genes due to the polar effect.…”
Section: Resultsmentioning
confidence: 99%
“…For example, some bacterial pathogens are capable of directly sensing and responding to host cytokines to facilitate their survival and transmission. 186,187 IL-1b is reported to accelerate the growth of virulent E. coli, 188 and human IFN-g can activate a virulent phenotype of P. aeruginosa. 189 Since the incorporation of unnatural amino acids into proteins or larger peptides has become more accessible by genetic code expansion or site-specific modification, the elucidation of protein-based host-pathogen interaction is now more easily accessible.…”
Section: Discussionmentioning
confidence: 99%
“…This study demonstrated that the CD5+ B cell subset is increased in LTB compared to HD and ATB. Moreover, LTB increases the frequency of IFN-γ-producing CD5+ B cells in response to proteins from Mtb, suggesting that the subpopulation CD5+ cells play an important role during the defense against Mtb, probably by the production of IFN-γ, a cytokine that is well-known for its capacity to activate the bactericide mechanism [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, we evaluated the CD23 expression on B cells, and it did not show differences (Figure S2A), following the CD23 expression assessed on the CD5+ B subset (Figure 6E). Despite the IL-10 and IL-4 production by the CD5+ B cell subset, the frequency of the CD5+CD23+ subpopulation was decreased in UC and LTB patients stimulated with TP [UC: unstimulated, 52 (44-65); TP, 19 , p < 0.0285; LTB: unstimulated, 59 (57-59); TP, 25 (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36), p < 0.0372]. On the contrary, DR-TB patients increased the CD5+ CD23+ B cells frequency in both TP and TL stimuli [unstimulated: 46 (32-60); TP: 77 (65-94), p < 0.0324; TL: 83 (73-88), p < 0.0267] (Figure 6F).…”
Section: Ltb Produces High Levels Of Il-10 and Il-4 In Response To Pr...mentioning
confidence: 99%